2022
DOI: 10.17066/tpdrd.1138273
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Body Image: Body Image Scale

Abstract: Bu çalışmanın amacı, ergenlik ve genç yetişkinlik dönemlerindeki bireylerin beden imajını ölçmeye ilişkin geçerliği ve güvenirliği kanıtlanmış bir ölçme aracı geliştirmektir. Araştırma grubunu 384 lise öğrencisi oluşturmuştur. Çalışmada uzman görüşüne başvurularak kapsam geçerliği; açımlayıcı (AFA) ve doğrulayıcı faktör analizi (DFA) uygulanarak yapı geçerliği test edilmiştir. Analizler kapsamında IBM SPSS Statistics v20.0 ve Lisrel 8.80 programlarından faydalanılmıştır. AFA sonucunda, toplam varyansın %62’sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…High scores obtained from the scale indicate that individuals have a negative body image. It has been shown to have very good construct validity (χ2/df = 1.72, RMSEA= .061, SRMR= .063, PGFI= .67, NFI= .90, NNFI= .94, PNFI= .7, GFI= .87, AGFI= .83; Saylan & Soyyiğit, 2022). In the current study, Cronbach's alpha internal consistency coefficient of the scale was found to be .76.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…High scores obtained from the scale indicate that individuals have a negative body image. It has been shown to have very good construct validity (χ2/df = 1.72, RMSEA= .061, SRMR= .063, PGFI= .67, NFI= .90, NNFI= .94, PNFI= .7, GFI= .87, AGFI= .83; Saylan & Soyyiğit, 2022). In the current study, Cronbach's alpha internal consistency coefficient of the scale was found to be .76.…”
Section: Methodssupporting
confidence: 52%
“…Body Image: The Body Image Scale, developed by Saylan & Soyyiğit (2022), is a five-point Likert type scale consisting of 21 items. It consists of four factors: negative perception of the body, evaluation sensitivity, positive perception of the body, and body change.…”
Section: Methodsmentioning
confidence: 99%